Regional Innovation in Arts Provision Spawned by COVID-19: "It Became a Lifeline for a Lot of People Who Are Stuck at Home" - Joanne Worsley; Josie Billington; Ekaterina Balabanova; Megan Watkins (Frontiers Media S.A., 2022)
Although the impact of the global COVID-19 pandemic on the arts and cultural sector due to the closure of galleries, museums, arts venues, and other cultural assets represents a significant health risk, new opportunities for arts and cultural engagement have arisen. Interviews with 24 representatives including service providers and creative practitioners from 15 arts and cultural organizations within the Liverpool City Region were conducted. The aim was to examine the impact of COVID-19 on arts and cultural provision and on organizations and people providing these services, as well as to understand the perceptions of service providers and practitioners of the effects on those whom arts and cultural organizations serve, including those who would usually access arts through formal healthcare routes (e.g., through collaboration with health partners). Interview data were analyzed using framework analysis. Four overarching themes were identified: Response: Closures, adaptations, and new directions; Challenges of online provision; Value of online provision; and the future of the arts. The arts and cultural sector has innovated rapidly, notably with accelerated digitalisation. Alternative provision has been "a lifeline" for vulnerable groups, such as those with mental health difficulties. Arts organizations have been most effective in reaching vulnerable, isolated and disadvantaged populations when they have worked in close collaboration with health and social care providers. The implementation of hybrid provision is an important move forward for the sector in light of our findings that alternative modes of provision are advantageous additions to service as usual. Given the increasing concerns about the mental health sequelae of the pandemic in the UK, arts and cultural engagement could play a pivotal role in the future recovery period.